Influence of geometric parameters of a pin joint of a carbon/epoxy composite plate on its load capacity - Krystek, Jan (Materiali in tehnologije, 2014)
The influence of geometric parameters of a composite pin joint on its load capacity was investigated. Numerical simulations of the pin joint were performed using the finite-element method in Abaqus. A material model with non-linear dependence of the shear stress/strain was used. A progressive-failure model was used in these simulations. The numerical model was validated by means of a comparison of experimental and numerical results. The behaviour of the pin joint was than further investigated using a calibrated FE model.
Keywords: zatič; spoji; kompoziti; metoda končnih elementov; finite element method; nosilnost; raztezek